Gambaran Pengetahuan Perawat Tentang Perawatan Paliatif di Siloam Hospitals Manado - Djamdin, Vika; Masi, Gresty; Meo, Maria Lupita Nena (Mapalus Nursing Science Journal, 2023)
Background. Knowledge of palliative care is needed by nurses in understanding and becoming the basis for the practice in providing palliative care both to patients and their families. Objective. To find out the level of knowledge of nurses about palliative care at Siloam Hospitals Manado. Method. This study used a quantitative descriptive design with a cross sectional approach. The research sample consisted of 136 respondents using total sampling techniques. The instrument used to measure nurses' level of knowledge about palliative care was the Palliative Care Quiz for Nurses-Indonesian Version (PCQN-I). Result. This study showed that respondents had a knowledge level of less than 6.6%, a sufficient knowledge level of 93.4%, and a good knowledge level of 0%. Based on the PCQN-I questionnaire, those who got the highest scores were in the pain management category and other symptoms with a mean value of 56.50, and those who got the lowest scores were in the psychosocial and spiritual care category with a mean value of 16.66. Discussion. In nursing practice, nurses focus more on patient complaints about visible symptoms and perceived pain, but patient complaints about psychological problems are poorly explained. Conclusion. The majority of respondents in this study had a sufficient level of knowledge towards palliative care. Therefore, there is a need for in-depth training related to palliative care through related hospital agencies. Keywords: Knowledge, Nurse, Palliative Care